Pengaruh Media Gambar Dalam Peningkatan Literasi Siswa Kelas III Di Sd Negeri 3 Ciharashas - Kuseptriani, Dea; Luthfia, Keisha Maureen (CV. SINAR HOWUHOWU, 2025)
The purpose of this study is to investigate how the use of visual media impacts the improvement of third-grade students' skills at SDN 3 Ciharashas in their literacy skills. To measure changes in students' literacy skills before and after the implementation of visual media, a quantitative descriptive pretest-posttest approach was used. The study results show that the use of visual media enhances students' literacy skills. This includes improvements in text comprehension, vocabulary, and reading interest. Previous studies indicate that visual media can improve elementary school students' literacy skills. These findings are consistent with this discovery. Therefore, the use of visual media can be an effective approach to improve students' literacy skills in elementary schools.